A review of the biology and therapeutic implications of cancer-associated fibroblasts (CAFs) in muscle-invasive bladder cancer - Burley, Amy; Rullan, Antonio; Wilkins, Anna (Frontiers in Oncology, 2022)
Cancer-associated fibroblasts (CAFs) play a fundamental role in the development of cancers and their response to therapy. In recent years, CAFs have returned to the spotlight as researchers work to unpick the mechanisms by which they impact tumour evolution and therapy responses. However, study of CAFs has largely been restricted to a select number of common cancers, whereas research into CAF biology in bladder cancer has been relatively neglected. In this review, we will explore the basics of CAF biology including the numerous potential cellular origins of CAFs, alongside mechanisms of CAF activation and their diverse functionality. Where possible, we will describe CAFs in the setting of bladder cancer, detailing their role in disease progression. In addition, we will highlight some of the landmark papers describing CAF heterogeneity. We will draw from findings in other common cancers to identify key therapeutic challenges associated with CAF biology and suggest areas which warrant further exploration in bladder cancer. Of relevance, we will describe a variety of strategies used to target CAFs and the signalling pathways that regulate their activation. In doing so, we will explore therapeutic options that may help to improve the current poor survival outcomes in bladder cancer which sadly remain largely unchanged over recent decades.